DEVELOPMENT OF CORPORATE MARKETING COMMUNICATION (CMC) BRANDING MODEL IN IAIN TULUNGAGUNG: TOWARD THE ERA OF WORLD CLASS UNIVERSITY - Agus Purwowidodo; Muhamad Yasin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
The study describes and analyzes the use of corporate marketing communication strategies towards Higher Education at the international level. This study used a qualitative descriptive method, with the research site at IAIN Tulungagung. The research subjects are members of the academic community, teaching staff, education staff and stakeholders. The research period was for the 2018/2019 academic year. The results showed that the typology of the marketing or promotion model used collaboration between internal parties (academics, stakeholders) and external parties (institutions, channel partners, media, government, industrial bodies and institutions, the educational community and the general public). Its implementation uses corporate advertising, sponsorship, sales presentations, online activities, branding, corporate advertising, press releases, press conferences, events, and awards. The study implications deal with the increase in: (1) Higher Education Identity, Image, Reputation; (2) Higher Education Social Responsibility (CSR); (3) media relation effectiveness; (4) more efficient marketing communications; (5) the more intensive Internal Communication System; (6) investor relation improvement; (7) conducive relations with the Government, and (8) the reliability in overcoming crisis communication. These have an impact on improving the quality of IAIN Tulungagung toward the level of International Higher Education.